1997
DOI: 10.1073/pnas.94.25.13475
|View full text |Cite
|
Sign up to set email alerts
|

Bidirectional binding of the TATA box binding protein to the TATA box

Abstract: By selective attachment of a DNA cleavage agent to specific residues in the yeast TATA box binding protein (yTBP), we demonstrate that, in solution, yTBP binds to the TATA boxes of both the adenovirus major late promoter and the yeast CYC1 promoter with only a modest preference in orientation and binds well to several overlapping binding sites. The general factors TFIIA and TFIIB each increase the rotational and translational selectivity of yTBP but are not sufficient, at least individually, to confer a unique… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
71
1
2

Year Published

1998
1998
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(82 citation statements)
references
References 31 publications
(41 reference statements)
8
71
1
2
Order By: Relevance
“…If TBP binds with a preferred orientation appropriate for PIC assembly, FeBABE tethered to the C-terminal stirrup is predicted to preferentially cleave the DNA at the upstream edge of the TATA box and farther upstream with one helical turn periodicity (7,8). Indeed, FeBABE cleavage was seen for the top strand of the AdMLP at the upstream end of the TATA box and one helical turn farther up the DNA (Fig.…”
Section: Dna Downstream Of Tata Is Required For Mot1mentioning
confidence: 99%
See 2 more Smart Citations
“…If TBP binds with a preferred orientation appropriate for PIC assembly, FeBABE tethered to the C-terminal stirrup is predicted to preferentially cleave the DNA at the upstream edge of the TATA box and farther upstream with one helical turn periodicity (7,8). Indeed, FeBABE cleavage was seen for the top strand of the AdMLP at the upstream end of the TATA box and one helical turn farther up the DNA (Fig.…”
Section: Dna Downstream Of Tata Is Required For Mot1mentioning
confidence: 99%
“…Because TBP stirrups bind at the ends of the TATA box sequence, the location of DNA cleavage reveals the orientation of the bound protein (8). If TBP binds with a preferred orientation appropriate for PIC assembly, FeBABE tethered to the C-terminal stirrup is predicted to preferentially cleave the DNA at the upstream edge of the TATA box and farther upstream with one helical turn periodicity (7,8).…”
Section: Dna Downstream Of Tata Is Required For Mot1mentioning
confidence: 99%
See 1 more Smart Citation
“…This behavior of TFIIB not only provides strong support for the HBV composite P(A)S-TATA box in sustaining promoter characteristics but also was helpful for mapping the orientation of this TATA box (27). It was reported that the TATA box can in fact act bidirectionally, and the involvement of auxiliary TFIIA and TFIIB is essential to determine the correct orientation (7). Based on these data we defined the TATA box orientation to be at the viral positive strand, where all the other viral promoters have been mapped.…”
Section: Discussionmentioning
confidence: 99%
“…Some functions long thought to be unidirectional, such as promoterdirected gene transcription, have been recently found to be bidirectional (22,23). The structural basis for this bidirectional transcription remains to be established, but could be rooted in the bidirectional binding of transcription regulatory proteins as well as the TATA box-binding protein at their recognition sites (24).…”
Section: Discussionmentioning
confidence: 99%